2016
DOI: 10.1097/mnh.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of bone mineral disorders in chronic kidney disease and end stage renal disease

Abstract: Purpose of review This review summarizes recent studies on chronic kidney disease-mineral bone disorders, with a focus on new developments in disease management. Recent findings The term chronic kidney disease-mineral bone disorder has come to describe an increasingly complex network of alterations in minerals and skeletal disorders that contribute to the significant cardiovascular morbidity and mortality seen in patients with chronic kidney disease and ESRD. Clinical studies continue to suggest associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
14
0
2
Order By: Relevance
“…Decreased GFR results in diminished renal phosphorus excretion which, in combination with the reduced levels of vitamin D, eventually lead to hypocalcemia, hyperphosphatemia, and hyperparathyroidism; detrimental effects follow, especially on bone and the vascular system . The secondary and tertiary hyperparathyroidism observed in CKD patients is associated with an increased risk of high‐turnover bone disease, adynamic bone disease, vascular and valvular calcification, calciphylaxis, metastatic calcification, and mortality, depending on the nature of the hyperparathyroidism …”
Section: Introductionmentioning
confidence: 99%
“…Decreased GFR results in diminished renal phosphorus excretion which, in combination with the reduced levels of vitamin D, eventually lead to hypocalcemia, hyperphosphatemia, and hyperparathyroidism; detrimental effects follow, especially on bone and the vascular system . The secondary and tertiary hyperparathyroidism observed in CKD patients is associated with an increased risk of high‐turnover bone disease, adynamic bone disease, vascular and valvular calcification, calciphylaxis, metastatic calcification, and mortality, depending on the nature of the hyperparathyroidism …”
Section: Introductionmentioning
confidence: 99%
“…Dialysis clearance of fetuin appears to be low (<15%), and similar with NHD and HDF. Retinol binding protein (21 kDa) is associated with insulin resistance and FGF23 (30 kDa) is thought to be a marker of chronic kidney disease and phosphate excess . High levels of these two markers may contribute to vascular disease and cardiac mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Retinol binding protein (21 kDa) is associated with insulin resistance 23 and FGF23 (30 kDa) is thought to be a marker of chronic kidney disease and phosphate excess. 24 High levels of these two markers may contribute to vascular disease and cardiac mortality. 23,24 Our study showed there was no significant difference in clearances of retinol binding protein with both modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) As a result, CKD mineral and bone disorder (CKD-MBD) is a common metabolic complication, 2) and contributes to the high cardiovascular morbidity and mortality seen in CKD patients. 3) Phosphate binders (PBs) are frequently prescribed to hemodialysis (HD) patients to prevent development of CKD-MBD. However, this often causes a higher pill burden.…”
Section: Introductionmentioning
confidence: 99%